Natural variations in grain length 10 (GL10) regulate rice grain size. (May 2022) - Zhan, Penglin; Ma, Shuaipeng; Xiao, Zhili; Li, Fangping; Wei, Xin; Lin, Shaojun; Wang, Xiaoling; Ji, Zhe; Fu, Yu; Pan, Jiahao; Zhou, Mi; Liu, Yue; et al.
Abstract: Grain size is an important determinant of grain weight and yield in rice. Although several genes related to grain size have been identified, natural variations in these genes that affect grain size are poorly characterized. Here, we describe the grain length QTL GL10, encoding MADS56, which positively regulates grain length and grain weight. A natural allelic variation of NIL- gl10, containing an ∼1.0-kb deletion in the first exon that abolishes its transcription, results in shorter grain length, lower grain weight and delayed flowering in gl10 plants. The knockout of GL10 in the HJX74 background leads to grain phenotypes similar to that of NIL- gl10, while overexpression of GL10 results in increased grain length and weight and earlier heading date. GL10 regulates grain length by promoting greater longitudinal cell growth in the grain glume. Additionally, GL10 participates in the regulation of gibberellic acid (GA) signaling pathway genes in young panicle tissues. Analysis of GL10 haplotypes shows obvious divergence between the japonica and indica lineages. Our findings reveal an allelic variation of GL1 0 that may explain differences in grain length among modern cultivars and could be used to breed rice varieties with optimized grain shape.